2020
DOI: 10.17533/udea.iee.v38n3e14
|View full text |Cite
|
Sign up to set email alerts
|

Presence of the Reflective and Critical Thinking Capacity in Nursing Curricula in Iberian America

Abstract: Objective. The objective was to identify the presence of the capacity for reflexive-critical thinking or similar, in Nursing Curricula in Iberian America. Methods. The article gathers the results of one of the objectives of the macro-project developed by the Iberian American Network on Nursing Education Research, titled Strategies to develop reflective and critical thinking in nursing students: Iberian America situation. To achieve this, a descriptive and exploratory research was conducted with qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…A EPE, então, dimensionou seu cenário de prática de maneira eficiente, oportunizando ambientes educativos mais significativos, e a aprendizagem passou a ser significativa, com capacidade de reflexão frente às experiências vivenciadas pelo estudante. Isso cultivou o desenvolvimento do saber, por meio da experimentação contínua, apoiado na forma como o estudante detém o conhecimento e o aplica em uma tomada de decisão (17) . Assim, é possível afirmar que o trabalho docente praticado na EPE promoveu a possibilidade de construção de novos conhecimentos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A EPE, então, dimensionou seu cenário de prática de maneira eficiente, oportunizando ambientes educativos mais significativos, e a aprendizagem passou a ser significativa, com capacidade de reflexão frente às experiências vivenciadas pelo estudante. Isso cultivou o desenvolvimento do saber, por meio da experimentação contínua, apoiado na forma como o estudante detém o conhecimento e o aplica em uma tomada de decisão (17) . Assim, é possível afirmar que o trabalho docente praticado na EPE promoveu a possibilidade de construção de novos conhecimentos.…”
Section: Discussionunclassified
“…Alguns autores ressaltam que a organização curricular deve viabilizar a aquisição de conhecimento teórico e prático para desenvolver nos estudantes habilidades técnicas aplicáveis na prática, devendo promover a interdisciplinaridade dos conhecimentos e assegurar o enriquecimento do pensamento crítico e reflexivo na comunicação e tomada de decisão (3,17) .…”
Section: Discussionunclassified
“…Published by Sciedu Press curricula, and concluded that it is addressed, under various nominations, in most curricula. [83] In addition, another study, which assessed nursing programs in the Andes region, identified that CT is considered a cognitive, communicative and personal skill. [4] There are other investigations on CT in mental health, [84] in intensive and medical-surgical, [85] and in surgical nursing.…”
Section: Legend: Ct = Critical Thinkingmentioning
confidence: 99%